Noninvasive assessment of mitochondrial organization in three‐dimensional tissues reveals changes associated with cancer development. Issue 2 (5th June 2014) - Xylas, Joanna; Varone, Antonio; Quinn, Kyle P.; Pouli, Dimitra; McLaughlin‐Drubin, Margaret E.; Thieu, Hong‐Thao; Garcia‐Moliner, Maria L.; House, Michael; Hunter, Martin; Munger, Karl; Georgakoudi, Irene
<x xml:space="preserve">Abstract</x> Mitochondrial organization is often altered to accommodate cellular bioenergetic and biosynthetic demands. Changes in metabolism are a hallmark of a number of diseases, including cancer; however, the interdependence between mitochondrial metabolic function and organization is not well understood. Here, we present a noninvasive, automated and quantitative method to assess mitochondrial organization in three‐dimensional (3D) tissues using exclusively endogenous two‐photon excited fluorescence (TPEF) and show that mitochondrial organization reflects alterations in metabolic activities. Specifically, we examine the organization of mitochondria within live, engineered epithelial tissue equivalents that mimic normal and precancerous human squamous epithelial tissues. We identify unique patterns of mitochondrial organization in the different tissue models we examine, and we attribute these to differences in the metabolic profiles of these tissues. We find that mitochondria are clustered in tissues with high levels of glycolysis and are more highly networked in tissues where oxidative phosphorylation is more dominant. The most highly networked organization is observed within cells with high levels of glutamine consumption. Furthermore, we demonstrate that mitochondrial organization provides complementary information to traditional morphological hallmarks of cancer development, including variations in nuclear size. Finally, we present evidence that this automated quantitative analysis of endogenous TPEF images can identify differences in the mitochondrial organization of freshly excised normal and pre‐cancerous human cervical tissue specimens. Thus, this method could be a promising new modality to assess the role of mitochondrial organization in the metabolic activity of 3D tissues and could be further developed to serve as an early cancer clinical diagnostic biomarker.